Leuprolide Acetate Therapy in Luteinizing Hormone–Dependent Cushing's Syndrome - André Lacroix; Pavel Hamet; Jean‐Marie Boutin (1999)
Corticotropin-independent Cushing's syndrome is usually caused by cortisol-secreting adrenal adenomas, carcinomas, or (rarely) bilateral adrenal hyperplasia. In some patients with this syndrome, the excess secretion of cortisol is caused by abnormal adrenal expression and function of receptors for various hormones, including gastric inhibitory polypeptide,1–6 vasopressin,7–9 β-adrenergic agonists,10 and interleukin-1.11 These findings suggest that diverse other hormone receptors could be implicated in other patients.12 We describe a woman with bilateral adrenal hyperplasia and corticotropin-independent Cushing's syndrome that was clinically manifested transiently during her pregnancies and became constant only after menopause. The patient's cortisol secretion was stimulated by luteinizing hormone . . .